2012
DOI: 10.1371/journal.pone.0035391
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Benefits of Height: Strength, Dominance, Social Concern, and Knowledge among Bolivian Native Amazonians

Abstract: Research in industrial countries suggests that, with no other knowledge about a person, positive traits are attributed to taller people and correspondingly, that taller people have slightly better socioeconomic status (SES). However, research in some non-industrialized contexts has shown no correlation or even negative correlations between height and socioeconomic outcomes. It remains unclear whether positive traits remain attributed to taller people in such contexts. To address this question, here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In the Tsimane' adults, there is no association between height and perceptions of dominance and intelligence (Undurraga et al, 2012). According to Godoy et al (2010), height is furthermore not associated with income or wealth in this society.…”
Section: Discussionmentioning
confidence: 90%
“…In the Tsimane' adults, there is no association between height and perceptions of dominance and intelligence (Undurraga et al, 2012). According to Godoy et al (2010), height is furthermore not associated with income or wealth in this society.…”
Section: Discussionmentioning
confidence: 90%
“…We did not measure the social and household context in which stunting occurred. In an earlier study, we found that adult Tsimane' attributed more positive traits to taller children, but not to taller adults (Undurraga et al, ). Some of the adverse associations between stunting and child human capital might have taken place because parents invested less in stunted than in nonstunted children, for example, reinforcing a child's endowments.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the tallness stereotype may not be as intrinsic and universal as it seemsthis conclusion was not supported by the results of studies conducted in traditional societies (Undurraga et al 2012;. Members of traditional societies, such as foraging-farming Tsimane' from Amazonia, attributed positive traits to taller children, but not adults (Undurraga et al 2012), the Yali tribe of Papua favor tallness in men to a far lesser extent than the Western societies do , and in a semi-nomad population of Himba in Namibia the largest proportion of the participants preferred a partner with a height equal to one's own .…”
Section: Introductionmentioning
confidence: 79%